Descriptive Study of Body Mass Index (BMI), Waist and Blood Pressure in Students of Doctor Education Study Program, Faculty of Medicine Universitas Sriwijaya - Anggun Fitri Utami; Wardiansah (Sriwijaya Journal of Medicine, 2020)
Introduction : The Descriptive Study about Body Mass Index (BMI), Waist Circumference and Blood Pressure on Medical Students in Medical Faculty of Universitas Sriwijaya. Body mass index (BMI) is a measurementindicator recommended by WHO to identify the nutritional status of an individual. Methods:Body weight and height measurements were taken to calculate the value of body mass index (BMI), measurement of waist circumference and measurement of blood pressure on students at the Faculty of Medicine Universitas Sriwijaya class of 2016. The value of BMI in the category of overweight and obesity is most at the age of 20-21 years (20.6%) and in female (14%). The value of waist circumference in the abnormal category is most at the age of 20-21 years in men (5.3%) and women (11.81%). The value of blood pressure that has prehypertension and first degree hypertension isin students aged 20-21 years (20.2%) and most in men (14%). Results: The blood pressure values included in the pre-hypertension and first-degree hypertension categories were most on the BMI valuesin the overweight and obese categories (18.8%) and in the waist circumference inthe medium and large categories (13.81%). The distribution of research subjects based on BMI and waist circumference that exceeds the normal value is most at the age of 20-21 years and in women. The distribution of research subjects based on blood pressure that experienced pre-hypertension and first degree hypertension was most at the age of 20-21 years and in men. Conclusion :The distribution of research subjects based on blood pressure that experienced pre-hypertension and first degree hypertension at most in the value of BMI and waist circumference that exceeds the normal value.